Role of Empathy in Engineering Education and Practice in North America - Eric Wilson; Phalguni Mukhopadhyaya (MDPI AG, 2022)
Does engineering design education in North America prepare students to address the major issues of our time? In today's political and social climate, engineers are part of multi-disciplinary teams tasked with finding solutions to complex issues like poverty, climate change, the housing affordability crisis, resource depletion, and water shortages. By definition, these problems are "wicked". If engineers are to play a role in addressing issues that exist at the intersection of technology and society, they must have a deep understanding of both technical competencies and of human factors. They must have the ability to empathize. In consideration of today's social, political, and environmental challenges, it has never been more important to instill social competencies into engineering education and practice, particularly around engineering design. This paper analyzes the previous literature on empathy in engineering education in North America and synthesizes the data to present the conceptualization that engineers have of empathy in education and practice.